Optimization of Cryogenic Grinding as a Hair Sample Preparation Technique for Heavy Metal Concentration Analysis - Andayani, I Gusti Ayu Sri; Retnowati, Indah; Mariana, Baiq; Ismillayli, N; Ekawanti, Ardiana; Ayunda, Rahmah Dara (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effectiveness of cryogenic grinding as a hair sample preparation technique and to compare heavy metal analysis results obtained using Energy Dispersive X-ray (EDX) and Atomic Absorption Spectrophotometry (AAS). Hair samples were collected from five residents of Sekotong and analyzed for Cd, Hg, and Pb content. Data were analyzed descriptively and compared using the Friedman test. The results indicated that AAS consistently yielded higher metal concentrations than EDX. Cd concentrations measured by AAS, EDX of powdered hair, and EDX of intact hair were 0.00656 mg/kg, 0.00130 mg/kg, and 0.00010 mg/kg, respectively. For Hg, the corresponding measurements were 0.00380 mg/kg, 0.00212 mg/kg, and 0.00362 mg/kg, whereas Pb exhibited the largest disparity, with 0.12930 mg/kg for AAS, 0.00224 mg/kg for EDX of powdered hair, and 0.06978 mg/kg for EDX of intact hair. The high variability, particularly in Pb measurements, suggests that heterogeneity in metal distribution and surface contamination affect EDX readings of intact hair. Cryogenic grinding yielded a more homogeneous particle distribution, resulting in EDX measurements of powdered hair that were more representative and numerically closer to AAS results than measurements of intact hair. Although differences were not statistically significant (p > 0.05), these findings support the use of cryogenic grinding to enhance the accuracy of hair-based heavy metal analysis. Furthermore, this method has the potential to reduce the use of destructive chemicals and hazardous waste, making it a safer and more sustainable alternative for community biomonitoring in areas affected by heavy metal contamination.